Variabel-Variabel yang Memengaruhi Angka Buta Huruf (ABH) di Provinsi Papua Tahun 2020 - Bertha Sani Lake; Efri Diah Utami (Seminar Nasional Official Statistics, 2022)
Education is one of the absolute needs that must be met in human life. One of the targets of the fourth Sustainable Development Goals (SDGs) is ensure that all youth and some adults, both boys and girls, achieve literacy and numeracy skills. The high ABH is one of the crucial problems in the field of education that has not been resolved until now. Papua is the province with the highest ABH in Indonesia, which is 22.10 percent. This figure is very high compared to the national ABH which is 4.00 percent. Therefore, this study aims to determine the general description of ABH and what variables affect ABH in Papua Province in 2020. The analytical method used in this study is multiple linear regression. The results showed that the variables of School Readiness Rate (AKS), Elementary School Dropout Rate (APTS), number of schools and population had a significant effect on ABH.